2008
DOI: 10.2478/s11756-008-0134-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a xylanase from a thermophilic strain of Anoxybacillus pushchinoensis A8

Abstract: A facultatively anaerobic, thermophilic, xylanolytic bacterium was isolated from a sample collected from the Diyadin Hot Springs, Turkey. According to morphological, biochemical and molecular identification, this new strain was suggested to be representative of the Anoxybacillus pushchinoensis and it was designated as Anoxybacillus pushchinoensis strain A8. It exhibited 97% similarity to 16S rRNA gene sequence of A. pushchinoensis and 77% DNA homology by DNA-DNA hybridization studies. Q-sepharose and CM-sephar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…The optimization of medium and culture conditions for maximum xylanase production was carried out by stepwise variation of physicochemical parameters of growth conditions of A. kamchatkensis NAST-PD13. Initially, the bacterial isolate was grown in various MSM containing 0.5% xylan as reported previously (Nakamura et al, 1993 ; Kacagan et al, 2008 ; Maki et al, 2011 ; Padilha et al, 2015 ) (data not shown). Nakamura and Horikoshi basal medium had been routinely used for the isolation of xylanase producing microorganisms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimization of medium and culture conditions for maximum xylanase production was carried out by stepwise variation of physicochemical parameters of growth conditions of A. kamchatkensis NAST-PD13. Initially, the bacterial isolate was grown in various MSM containing 0.5% xylan as reported previously (Nakamura et al, 1993 ; Kacagan et al, 2008 ; Maki et al, 2011 ; Padilha et al, 2015 ) (data not shown). Nakamura and Horikoshi basal medium had been routinely used for the isolation of xylanase producing microorganisms.…”
Section: Methodsmentioning
confidence: 99%
“…Gels were then stained with 0.1% Congo red for 10 min and destained with 1 M NaCl until zones of clearing were seen. The gels were fixed with 5% acetic acid and photographed (Kacagan et al, 2008 ).…”
Section: Methodsmentioning
confidence: 99%
“…Menaquinone 6 (MK-6) is the major respiratory quinone, while C 15 : 0 , iso-C 15 : 0 , iso-C 15 : 1 G, iso-C 15 : 0 3-OH, summed feature 3 (C 16 : 1 v7c and/or C 16 : 1 v6c), iso-C 16 : 0 3-OH, iso-C 17 : 1 v9c and iso-C 17 : 0 3-OH are the predominant fatty acids, and the genomic DNA G+C contents are in the range of 30-52 mol% (Bernardet & Bowman, 2006Bernardet et al, 1996). Species of the genus Flavobacterium have been isolated from various habitats, including seawater (Bhumika et al, 2013;Fu et al, 2011;Yi et al, 2005), freshwater (Chen et al, 2013;Kacagan et al, 2013;Kang et al, 2013;Kim et al, 2014;Lee et al, 2013;Qu et al, 2009), high-arsenic sediments (Ao et al, 2014), wastewater (Aslam et al, 2005;Liu et al, 2010;Yoon et al, 2009), soil (Dong et al, 2013a, b;Kim et al, 2006), farmland (Chen et al, 2014;Kim et al, 2006;Liu et al, 2008), river sludge (Zhang et al, 2015a), marine sediment (Fu et al, 2011;algae (Miyashita et al, 2010;Nedashkovskaya et al, 2014), compost (Kim et al, 2011(Kim et al, , 2012a, rhizosphere soil (Madhaiyan et al, 2010;Son et al, 2013;Xiao et al, 2011;Zhang et al, 2015b), a glacier (Zhang et al, 2006) and a plant (Kämpfer et al, 2015).…”
mentioning
confidence: 99%
“…These thermozymes have been used in a number of industrial applications as they possess thermal stability to harsh industrial processes at high temperatures (Demirjian et al, 2001). Thermophilic bacilli are the natural source of many thermostable enzymes, and of those from thermophilic bacilli, some thermostable enzymes belonging to species from the genus Anoxybacillus such as amylase (Poli et al, 2006), glucosidase (Cihan et al, 2009), esterase (Colak et al, 2005), aldolase (Ertunga et al, 2007), proteinase (Lavrenteva et al, 2009) and xylanase (Kacagan et al, 2008) have been well characterized.…”
Section: Introductionmentioning
confidence: 99%